(untitled) (Revista Argentina de Cirugía, 2021)
Tracheobroncomalacia is a disease of the central airway due to weakness of the wall with dynamic narrowing of the lumen of the trachea and mainstem bronchi during exhalation. It produces chronic symptoms that can progress to severe respiratory failure, often misdiagnosed as asthma or chronic obstructive pulmonary disease (COPD). We report the case of a 70-year-old female patient with a history of rheumatoid arthritis and multiple hospitalizations for recurrent respiratory infections over the past 3 years.